Effect of a “Dual Trigger” Using a GnRH Agonist and hCG on the Cumulative Live-Birth Rate for Normal Responders in GnRH-Antagonist Cycles - Gao, Fumei; Wang, Yanbin; Fu, Min; Zhang, Qiuxiang; Ren, Yumeng; Shen, Huan; Han, Hongjing (Frontiers in Medicine, 2021)
“Dual triggering” for final oocyte maturation using a combination of a gonadotropin-releasing hormone agonist (GnRHa) and human chorionic gonadotropin (hCG) can improve clinical outcomes in high responders during in vitro fertilization–intracytoplasmic sperm injection (IVF–ICSI) GnRH-antagonist cycles. However, whether this dual trigger is also beneficial to normal responders is not known. We retrospectively analyzed the data generated from 469 normal responders from 1 January to 31 December 2017. The final oocyte maturation was undertaken with a dual trigger with a GnRHa combined with hCG (n = 270) or hCG alone (n = 199). Patients were followed up for 3 years. The cumulative live-birth rate was calculated as the first live birth achieved after all cycles having an embryo transfer (cycles using fresh embryos and frozen–thawed embryos) among both groups. Women in the dual-trigger group achieved a slightly higher number of oocytes retrieved (11.24 vs. 10.24), higher number of two-pronuclear (2PN) embryos (8.37 vs.7.67) and a higher number of embryos available (4.45 vs.4.03). However, the cumulative live-birth rate and the all-inclusive success rate for assisted reproductive technology was similar between the two groups (54.07% vs.59.30%). We showed that a dual trigger was not superior to a hCG-alone trigger for normal responders in GnRH-antagonist cycles in terms of the cumulative live-birth rate.